Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 831 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Draba oblongata R.Br. ex DC." ] } The dataset includes 831 records from 39 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0183588-230224095556074/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences